Penganganan Dan Pencegahan Hipertensi Di Guwosari Pajangan Bantul DIY - nova maulana (J.Abdimas: Community Health, 2022)
Hypertension is one of the diseases that are common in the community. Mortality due to hypertension in Indonesia is very high. The case of hypertension is quite common, especially in the elderly. As for the understanding of hypertension and the prevention and initial treatment of hypertension is still not yet known by the citizens of the elderly. A preventive measure in the form of promotive and preventive currently be a priority. The increase of public understanding about the disease of hypertension is expected to reduce the morbidity and mortality of hypertensive disease. The purpose of this activity is to provide an understanding of how the management and prevention of hypertension early in guwosari pajangan Bantul DIY. This education Program was held in the Village guwosari pajangan Bantul yogyakarta in February 2022 in the form of lectures, question and answer and blood pressure checks. Activities running, the participants were enthusiastic to listen and ask various things about hypertension that is not yet understood. So that participants can really know and understand the causes, symptoms, risk factors, prevention and treatment of hypertension. Similarly, it is expected that elderly residents can perform routine checks of blood pressure independently or in a health care facility. Keywords: Hypertension, prevention, treatment